Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

The influence of precipitation pulses on soil respiration – Assessing the “Birch effect” by stable carbon isotopes - Unger, Stephan; Máguas, Cristina; Pereira, João S.; David, Teresa S.; Werner, Christiane (Soil Biology and Biochemistry, 2010)
Sudden pulse-like events of rapidly increasing CO2-efﬂux occur in soils under seasonally dry climates in response to rewetting after drought. These occurrences, termed “Birch effect”, can have a marked inﬂuence on the ecosystem carbon balance. Current hypotheses indicate that the “Birch” pulse is caused by rapidly increased respiration and mineralization rates in response to changing moisture conditions but the underlying mechanisms are still unclear. Here, we present data from an experimental ﬁeld study using straight-forward stable isotope methodology to gather new insights into the processes induced by rewetting of dried soils and evaluate current hypotheses for the “Birch“-CO2-pulse. Two irrigation experiments were conducted on bare soil, root-free soil and intact vegetation during May and August 2005 in a semi-arid Mediterranean holm oak forest in southern Portugal. We continuously monitored CO2-ﬂuxes along with their isotopic compositions before, during and after the irrigation. d 13 C signatures of the ﬁrst CO2-efﬂux burst, occurring immediately after rewetting, ﬁt the hypothesis that the “Birch” pulse is caused by the rapid mineralization of either dead microbial biomass or osmoregulatory substances released by soil microorganisms in response to hypo-osmotic stress in order to avoid cell lyses. The response of soil CO2-efﬂux to rewetting was smaller under mild (May) than under severe drought (August) and isotopic compositions indicated a larger contribution of anaplerotic carbon uptake with increasing soil desiccation. Both length and severity of drought periods probably play a key role for the microbial response to the rewetting of soils and thus for ecosystem carbon sequestration.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Birch effect; d13C; Irrigation experiment; Mediterranean woodland; Soil respiration; Stable isotopes